Web service composition using fluent calculus. (7th July 2010) - Salomie, Ioan; Chifu, Viorica Rozina; Harsa, Ioana; Gherga, Marius
This paper presents a new approach for automatic web service composition based on the formalism of fluent calculus. In our approach, the service composition process is viewed as an AI planning problem in the fluent calculus. To semantically describe the services, we have used a domain ontology, which is then translated into a fluent calculus knowledge base, necessary for the composition-planning phase. For verifying the composed services, the Label Transition System Analyser formalism is used. The paper also presents an experimental prototype for the fluent-calculus-based service composition and demonstrates its effectiveness with the help of an application scenario from the social-event planning domain.